Description of Mycobacterium pinniadriaticum sp. nov., isolated from a noble pen shell (Pinna nobilis) population in Croatia - Špičić, Silvio; Duvnjak, Sanja; Papić, Bojan; Reil, Irena; Zrnčić, Snježana; Mihaljević, Željko; Naletilić, Šimun; Zupičić, Ivana Giovanna; Kompes, Gordan; Habrun, Boris; Mareković, Ivana; Zdelar-Tuk, Maja (Frontiers in Microbiology, 2023)
Shortly before the mass mortality event of the noble pen shell (Pinna nobilis) population in the southeastern Adriatic coast, two rapidly growing Mycobacterium strains CVI_P3 T (DSM 114013T, ATCC TSD-295T) and CVI_P4 were obtained from the organs of individual molluscs during the regular health status monitoring. The strains were identified as members of the genus Mycobacterium using basic phenotypic characteristics, genus-specific PCR assays targeting the hsp65 and 16S rRNA genes and the commercial hybridization kit GenoType Mycobacterium CM (Hain Lifescience, Germany). MALDI-TOF mass spectrometry did not provide reliable identification using the Bruker Biotyper Database. Genome-wide phylogeny and average nucleotide identity (ANI) values confirmed that the studied strains are clearly differentiated from their closest phylogenetic relative Mycobacterium aromaticivorans and other validly published Mycobacterium species (ANI ≤ 85,0%). The type strain CVI_P3 T was further characterized by a polyphasic approach using both phenotypic and genotypic methods. Based on the phenotypic, chemotaxonomic and phylogenetic results, we conclude that strains CVI_P3 T and CVI_P4 represent a novel species, for which the name Mycobacterium pinniadriaticum sp. nov. is proposed.